Circuits of Exploitation and Networks of Resistance: Towards an Anti-Racist Intersectional Global Nineteenth Century. Issue 1 (1st June 2022) - Thelwell, Chinua
Abstract : This essay argues that anti-racist intersectional perspectives should influence academic theorizing about the global nineteenth century. This is because twenty-first century scholarship is not created in a social bubble and scholars are currently living through a very dangerous time as exclusionary white nationalist movements have spread to many countries. This essay draws from Silencing the Past, an influential book in which Michel-Rolph Trouillot argues that knowledge production about history is almost always a political project. Given the aforementioned contexts, socially responsible twenty-first century scholars should continue denaturalizing racial and gender hierarchies in an attempt to build a better future based on the concepts of equal rights and equitable access to resources. The author offers his book, Exporting Jim Crow: Blackface Minstrelsy in South Africa and Beyond as a recent example of an anti-racist knowledge production project about the global nineteenth century. The essay ends with suggestions for future scholarship.